2014
DOI: 10.1111/maps.12246
|View full text |Cite
|
Sign up to set email alerts
|

Photodissociation of CO isotopologues: Models of laboratory experiments and implications for the solar nebula

Abstract: Abstract-CO photodissociation in the solar nebula and/or parent cloud has been proposed to be the mechanism responsible for forming the 16 O-poor reservoir of the calciumaluminum-rich inclusion (CAI) mixing line. However, laboratory experiments on CO photolysis found a wavelength dependence in the oxygen isotope ratios of the product O atoms, which was interpreted as proof that CO photolysis was not a viable mechanism. Here, I report photochemical simulations of these experiments using line-by-line CO spectra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 75 publications
(225 reference statements)
0
9
0
Order By: Relevance
“…However, their experiment and discussion did not convince most of the other researchers 1416 . Now it is generally agreed that self-shielding effect is the main reason of the massive isotope fractionation observed in the above experiment and also that in the solar system, while Thiemens´ experiment does have the effect of encouraging people to include the different photoabsorption and photodissociation cross sections for different CO isotopologues in their models, which has been proved to make the modeling results in closer agreement with the experimental measurements 17,18 . Compared to the absorption line positions, accurate absolute values of photoabsorption and photodissociation cross sections are much more difficult to be measured, thus continued recent efforts are being devoted to obtain more precise values of these for all the CO isotopologues in hope of further improving the photochemical modeling 1922 .…”
Section: Introductionmentioning
confidence: 63%
See 2 more Smart Citations
“…However, their experiment and discussion did not convince most of the other researchers 1416 . Now it is generally agreed that self-shielding effect is the main reason of the massive isotope fractionation observed in the above experiment and also that in the solar system, while Thiemens´ experiment does have the effect of encouraging people to include the different photoabsorption and photodissociation cross sections for different CO isotopologues in their models, which has been proved to make the modeling results in closer agreement with the experimental measurements 17,18 . Compared to the absorption line positions, accurate absolute values of photoabsorption and photodissociation cross sections are much more difficult to be measured, thus continued recent efforts are being devoted to obtain more precise values of these for all the CO isotopologues in hope of further improving the photochemical modeling 1922 .…”
Section: Introductionmentioning
confidence: 63%
“…This contradicts with the prediction by photochemical models which only consider the self-shielding effect 13 . Being stimulated by this experimental work, Lyons performed a detailed quantitative simulation, and found that pure self-shielding alone can account for the magnitude of the massive isotopic fractionation observed in the experiment, while consideration of other isotopic effects can definitely make the model more realistic, for example, the isotopic differences in dissociation probabilities can cause the slope increase observed in Thiemens’ experiment 18 . Even though the branching ratios of 12 C 17 O and 12 C 18 O have not been directly measured yet, the present experiment strongly implies that different relative amounts of excited 17,18 O atoms [O( 1 D)] might be possibly produced, especially when considering the fact that 13 C 16 O and 12 C 18 O have very similar reduced masses 35 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The existence of rare samples, more 16 O-rich than the Sun (Kobayashi et al 2003), is not impossible, but deserves more study. I find the combination of the 16 O-rich solar composition and some highly 16 O-depleted water (Sakamoto et al 2007) a compelling argument for photochemical self-shielding, indicating a plausible pathway for 17 O and 18 O atoms produced from CO dissociation to enter essentially all inner solar system materials (Lyons and Young 2005;Lyons 2013). One must admit, however, that the "essentially all" requirement is a problem for photochemical self-shielding and this has led to alternative models based on inherited differences in O isotopic composition between gas and dust in the original solar nebula materials (e.g., Krot et al 2010;Huss 2012).…”
Section: O Isotopes In the Solar Windmentioning
confidence: 93%
“…Unlike the earlier model that focused on symmetry or self-shielding of minor gas species such as O 3 , O 2 , and CO 2 (Thiemens & Heidenreich 1983;Navon & Wasserburg 1985), the new COSS model (e.g., Clayton 2002; Yurimoto & Kuramoto 2004;Lyons & Young 2005;Lyons 2014) focused on photochemical isotopic effects of major volatile species such as CO (second in abundance to H 2 in molecular clouds). The model tracks a parcel of dust and gas with an initially homogenous oxygen isotopic composition.…”
Section: O/mentioning
confidence: 99%